Project for the Internet - Ericksen, Linda (SELECT lab series., 1998)
For courses covering the Internet/World Wide Web and HTML. SELECT: Internet provides introductory level students with skill-building, hands-on exercises that will get them up and running on the Internet in no time! The focus is on a spiraled development approach that integrates all features of the Internet into a powerful resource package, rather than focusing on each component as a separate entity. Concepts learned from the first project on are extended in subsequent projects. An accompanying Internet Website is provided and constantly updated and mail robots are set up to automatically respond to students' practice e-mail messages. SELECT: Internet is not browser specific so anyone can use it! SELECT: Internet Explorer 4.0 focuses on the essentials of this browser from Microsoft using a non-technical, non-jargon approach. This text teaches students how to use the global network to communicate in real time across the planet and includes coverage of bundled mail and news programs. SELECT: Internet Explorer 4.0 is perfect for any multi applications or concepts plus applications course in which hands-on coverage of the Internet is included using the most recent Internet Explorer browser. The SELECT Lab Series is beautifully illustrated with an easy-to-follow, class tested pedagogical design incorporated in a series of skill-building, hands-on projects enhanced by numerous full-color screen captures. SELECT: Netscape Communicator 4.0 covers basic through more intermediate skills including searching the Web and using Internet phone, collaboration, and conferencing tools. It is also quick and easy to create a custom Right PHIT package and take advantage of deep discounts by combining titles from Prentice Hall's SELECT Lab Series and Computer Information Systems List.